2018
DOI: 10.17944/mkutfd.489778
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Poisoning Cases Hospitalized to Intensive Care Unit

Abstract: Amaç: Akut zehirlenmeler acil servis(AS)'lere başvurular arasında küçük ama önemli bir yer tutar. Bu çalışmada AS'de zehirlenme tanısı konan ve daha sonra yoğun bakıma (YB) yatırılan hastaların demografik ve klinik özelliklerini değerlendirmeyi amaçladık. Gereç ve Yöntem:Ocak 2009-Haziran 2015 tarihleri arasında AS'de zehirlenme tanısı alan ve YB'a yatırılan hastalar AS protokol defteri, adli raporlar, YB takip defteri ve hastane yazılım sistemi kullanılarak geriye dönükolarak tarandı. Veriler SPSS 16,0'kayded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…The studies revealed that in our country suicidal intoxications occur frequently among females 3,4,5 . In the study by Akgün et al 74.3 % of the total 70 patients included in the study were female (n=52), 25.7% were male (n=18), and age average was 29.54 ± 13.51 6 . The study by Çakmak reported that the sex distribution was 71.87% female and 28.13% male, and this was consistent with the data of Turkish National Drug and Poison Information Center in 2008 2 .…”
Section: Discussionmentioning
confidence: 96%
“…The studies revealed that in our country suicidal intoxications occur frequently among females 3,4,5 . In the study by Akgün et al 74.3 % of the total 70 patients included in the study were female (n=52), 25.7% were male (n=18), and age average was 29.54 ± 13.51 6 . The study by Çakmak reported that the sex distribution was 71.87% female and 28.13% male, and this was consistent with the data of Turkish National Drug and Poison Information Center in 2008 2 .…”
Section: Discussionmentioning
confidence: 96%
“…Çalışmamızda acil servise zehirlenme ile başvuran hastaların %67,3'ünün (33) kadın, %32,7'sının ( 16) ise erkek olduğu görüldü. Çalışmamızda cinsiyet ile zehirlenme vakaları arasındaki dağılımın literatürle uyumlu olarak kadın cinsiyette daha fazla olduğu tespit edildi [10][11][12] .…”
Section: Discussionunclassified
“…Çalışmada, en sık zehirlenmeye neden olan ilaç kullanımlarının, tekli ilaç kullanımlarına (%73,5) bağlı olduğu tespit edilirken. Yapılan benzer çalışmalarda da benzer sonuçlara ulaşılmıştır 10,14 . Ayrıca çalışmada zehirlenmeye neden olan ilaç etken grupları incelenmiş, analjezik ve paresetemol grubu ilaç zehirlenmeleri ile psikiatrik ilaçların daha fazla olduğu görülmüştür.…”
Section: Introductionunclassified
“…Childhood poisoning represents a significant health concern both globally and nationally, contributing to severe mortality and morbidity, with a high incidence of emergency service admissions and hospitalizations (1). The American Poison Control Center's records indicate that over two million children seek assistance from pediatric emergency services due to poisoning annually (2).…”
Section: Introductionmentioning
confidence: 99%